Fiscal Decentralization and Its Impact on Capital Expenditures and Economic Growth in Buru Regency - Tri Wahyuningsih; Indarwati Indarwati (JURNAL SAINS SOSIAL DAN HUMANIORA (JSSH), 2025)
The study aims to determine the effect of fiscal decentralization on economic growth in Buru Regency, both directly and indirectly through capital expenditure variables. The research method used is explanatory causality using the path analysis method and analysis tools in the form of the SPSS program. The data used in this study are secondary data sourced from BPS (Central Statistics Agency) from 2015 to 2024 in Buru Regency. The results of the study show that directly a) Fiscal decentralization has a negative and significant effect on capital expenditure; b) Fiscal decentralization has a positive and insignificant effect on economic growth. c) Capital expenditure has a negative and insignificant effect on economic growth in Buru Regency; d) The direct effect of fiscal decentralization on economic growth is very large compared to the indirect effect of fiscal decentralization on economic growth through capital expenditure variables. Thus, the Buru Regency regional government needs to strive to increase Regional Original Income (PAD) through innovations in levy collection, regional taxes, and management of Regionally-Owned Enterprises (BUMD) in order to increase the degree of regional fiscal decentralization.